490 An immuno-oncology census: assessment of clinician knowledge and educational needs in 2020. (10th December 2020) - Schrag, Janelle; Draper, Fitzgerald; Dawkins, Monique; Lucas, Lorna; Boehmer, Leigh
Abstract : Background: The landscape for clinician education in immuno-oncology (IO) has changed dramatically since the first approval of an immune checkpoint inhibitor (ICI) in 2011. Educational initiatives have had to evolve with the multitude of new IO approvals and indications, as well as continuous integration of these therapies in patient care. As such, an IO census survey was administered and analyzed to better assess the current knowledge and educational needs of the oncology care team at the start of a new decade in IO. Methods: In June 2020, the Association of Community Cancer Centers launched an online survey to its membership of multidisciplinary oncology providers. The survey included questions related to demographic information, current IO practices, and top priorities and challenges in IO. In August 2020, an interim, descriptive analysis was conducted on complete survey responses (n=38). Results: At the time of interim analysis, survey respondents represented the full multidisciplinary cancer care team (e.g., advanced practice providers [18%], pharmacists [16%], medical and surgical oncologists [14%]), as well as diverse practice settings (e.g., community cancer program [28%], physician practice [20%]). In addition, the majority (67%) of respondents treated more than 20 patients per week with immunotherapies across most cancer types. When assessing familiarity with IO agents, most respondents were 'moderately familiar' or 'extremely familiar' with ICIs (26% and 53%, respectively). However, many respondents were 'not at all familiar' or only 'slightly familiar' with chimeric antigen receptor (CAR) T-cell therapy (5% and 42%, respectively) and bispecific antibody therapies (16% and 42%, respectively). The top challenges (i.e., 'very challenging' or 'extremely challenging') for respondents included the expansion of indications for IO agents (45% and 11%, respectively), coordinating care with non-oncology providers (29% and 18%, respectively), and financial toxicity (32% and 26%, respectively). Regarding future education topics, respondents expressed most interest (i.e., 'very interested' or 'extremely interested') in biomarker and molecular testing (71% and 18%, respectively), patient access, advocacy, and financial impact (61% and 24%, respectively), and evidence, data, and publication updates (55% and 26%, respectively). Conclusions: These interim results from a representative cohort strongly indicate that clinicians desire more clinical and operational support on use of IO agents and associated testing, easing patients' and programs' associated financial strain, and coordinating care across specialties. Additional analysis will focus on if/how respondents' specific disciplines or practice settings influence the results.